1 μm few-cycle pulse generation in a single-stage gas-filled hollow core fiber. (October 2022) - Feng, Renyu; Peng, Yujie; Li, Yanyan; Li, Wenkai; Qian, Junyu; Shen, Liya; Leng, Yuxin; Li, Ruxin
Highlights: Obtain Spectra with width of about 400 nm by using a single-stage gas-filled HCF. Obtain 1 μm pulses with 7.7 fs pulse duration (2.2 optical cycle) and 0.92 mJ pulse energy. Provide highly stable few-cycle near-infrared pulses for strong field physics experiments. Abstract: We demonstrate a simple and compact spectral broadening system, which is based on a single-stage gas-filled hollow core fiber (HCF). In our experiment, the pulse duration of pulses from an ytterbium doped amplifier is compressed from 170 fs down to 7.7 fs by using a 3-m-long gas-filled HCF with a core diameter of 500 μm. The pulse energy before and after HCF is 2 mJ and 0.92 mJ respectively, corresponding to a transmission efficiency of 46%, resulting in peak power of near 0.1 TW. In addition, the energy fluctuation of the output pulse is about 0.5%(RMS) measured in one hour. Such ultrafast light source can provide high stable few-cycle near-infrared driving pulses for strong field physics experiments.